Fish-in-hole: rationally positioning palladium into traps of zeolite crystals for sinter-resistant catalysts. Issue 26 (14th March 2018) - Wang, Guoxiong; Xu, Shaodan; Wang, Liang; Liu, Zhiqiang; Dong, Xue; Wang, Lingxiang; Zheng, Anmin; Meng, Xiangju; Xiao, Feng-Shou
Abstract : A fish-in-hole strategy for preparing a sinter-resistant Pd nanoparticle catalyst was reported, which is achieved by controllable positioning of Pd nanoparticles individually at the traps of zeolite crystals. Abstract : A fish-in-hole strategy for preparing a Pd nanoparticle catalyst was reported, which is achieved by controllable positioning of Pd nanoparticles individually at the traps of zeolite crystals. This Pd catalyst was sinter-resistant under high-temperature calcination and CO oxidation, outperforming the conventional supported catalyst consisting of supported Pd nanoparticles synthesized via the traditional deposition method.